PELATIHAN KETERAMPILAN TEKNIK DASAR KONSELING BAGI GURU MADRASAH TSANAWIYAH ARIFAH GOWA - Ahmad Razak; Ahmad Yasser Mansyur; Basti Tetteng; Satriani Satriani; Nur Amalia Ramadhani; Almira Salsabila Wargadipura; Nurfadila Nurfadila (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
School is an educational institution that serves as a place for acquiring knowledge, shaping morals and character, as well as developing students' interests and talents. To fulfill these functions, every school requires a guidance counselor to assist in character formation and handle student issues within the school. However, due to limited guidance counselors, this aspect may not be fully maximized. The purpose of this activity is to equip teachers with the skills to provide counseling services to students, as it is known that the interaction between homeroom teachers and subject teachers with students is more frequent compared to guidance counselors. This workshop was attended by 14 teachers from MTs Arifah. The methods used in this workshop included lectures (material presentation), counseling practice through role play, and pre-test and post-test assessments on basic counseling techniques. Based on the conducted Basic Counseling Techniques Workshop, it was found that the participants experienced an increase in knowledge about basic counseling techniques, as evidenced by the results of the pre-test and post-test. In addition to the test results, the counseling abilities of the participants can also be observed from the observations during the role play counseling practice.